Zanzibar Poverty Assessment - World Bank (World Bank, Washington, DC, 2017)
Zanzibar recorded an important decline in urban poverty, while rural poverty did not change, and poverty increased on the island of Pemba Basic needs poverty and extreme poverty both declined by 4.5 and 1 percentage points, respectively, at the national level in Zanzibar since 2010. Consumption also increased disproportionately among the poor, yet the absolute gains accruing to the poor and people in the bottom 40 percent remained limited. Poverty reduction was concentrated in urban areas, which was the main driver for Zanzibar’s overall poverty reduction. The main drivers of such a reduction in poverty were increases in returns to both the education and economic activity of the poor. Despite these improvements, households with large families and dependents employed in agriculture, and with lower education and lower access to infrastructure, continued to suffer from prevalent poverty. Basic needs poverty rates showed higher poverty in Zanzibar than in Mainland, but poverty measures based on the international line revealed lower poverty in Zanzibar. The services sector (including trade and public administration) accounted for a significantly larger share of employment in Zanzibar than in Mainland, while employment in agriculture was considerably higher in the latter. Besides being more diversified than in Mainland, the labor market in Zanzibar also offered higher incomes. In both Zanzibar and Mainland, less-educated workers were generally concentrated in agricultural employment, while those with superior education were engaged in the services sector. Middle skilled workers with lower secondary education were more engaged in trade, the private services sector, and manufacturing; while higher educated workers, with upper secondary and university degrees, were more involved in wage employment, mainly in public administrations.